Soil microbial communities alter conspecific and congeneric competition consistent with patterns of field coexistence in three Trifolium congeners. (13th August 2018) - Siefert, Andrew; Zillig, Kenneth W.; Friesen, Maren L.; Strauss, Sharon Y.
Abstract: Coexistence and diversity in plant communities depend upon outcomes of plant competition. Competition and coexistence can be mediated by abiotic soil nutrient differences as well as by soil microbial communities. The latter effects occur through various mechanisms including negative plant–soil feedbacks, when plants foster the build‐up of specialized pathogenic microbes, which ultimately reduce conspecific, but not heterospecific, densities. Microbial mutualists can have generalized associations with host plants, and by associating with multiple species might affect coexistence by conferring different levels of benefit to hosts. We examined the effects of abiotic differences and soil microbial communities, including mutualistic nitrogen‐fixing rhizobial bacteria, on coexistence processes and asked whether these interactions inform patterns of co‐occurrence in natural communities. We measured plant–soil feedbacks in the greenhouse for three native Trifolium species that either highly co‐occurred or were spatially repulsed at our field site. Using size‐fractioned soil microbial inocula prepared from field‐collected soils, we explored the effect of soil microbes on nodulation and the outcome of competition (relative interaction intensity). We also examined the effects of soil origin (home vs. away soil) on the outcome of competition between species. Soil microbes had strong positive effects on plant growth and nodulation. Microbes in general reduced the strength of plant competition relative to competition in sterilized soil and altered the relative strength of interactions with conspecific vs. congeneric neighbours, which often occurred in ways predicted to enhance coexistence. In one pair of highly co‐occurring Trifolium, competition was strong in sterilized soils, but these species facilitated one other in the presence of the full microbial community. The net effect of these microbes in general reduced competition while also increasing performance over that in sterilized soil, suggesting a role for soil microbial mutualists in host coexistence. Synthesis . Our results demonstrate that interactions between plants and diverse soil communities can alter plant–plant interactions and plant–soil feedbacks. They may increase niche differences and equalize fitness differences in ways consistent with observed co‐occurrence in the field. Abstract : Soil microbes can influence coexistence of close relatives in multiple ways simultaneously, by altering plant–soil feedbacks and plant‐plant interactions. In three closely related Californian Trifolium species, these largely mutualistic microbial communities influenced fitness equality and niche differences in ways consistent with patterns of coexistence in the field.